Temperature effect on the biological activity of Bifidobacterium longum CRL 849 and Lactobacillus fermentum CRL 251 in pure and mixed cultures grown in soymilk - Garro, Marisa Selva (2004)
The influence of temperature on the growth and biological activity of two probiotic strains (Bifidobacterium longum CRL 849 and Lactobacillus fermentum CRL 251) as pure and mixed cultures in soymilk (SM) were evaluated. Maximum growth was observed at 37°C in both mixed and pure cultures. In a product prepared with the mixed culture (1:1) at 37°C, the amount of lactic acid produced was approximately 55 mmol l-1 after 24 h with a slow production rate (2.8 mmol l-1 h-1); the formation of acetic acid was higher with respect to pure cultures (82.01 mmol l-1 after 24 h), and final pH (24 h) was 5.0. About 85% of the total amount of sugars in SM was reduced, mainly sucrose. Stachyose was reduced (71%) after 4 h of incubation. Maximum activity of alpha-galactosidase (alpha-gal) (13.2 U ml-1) was observed after 6 h. At 37°C the bifidobacterium strain was viable in mixed culture throughout the period assayed. At lower (30°C) or higher (42°C) temperatures, mixed culture showed slower growth and lower acid production in SM but the alpha-gal activity was stimulated at 30°C. © 2004 Elsevier Ltd. All rights reserved.